Committing to grow: The full impact of WTO accessions - André Brotto; Adam Jakubik; Roberta Piermartini; Fulvio Silvy (World Trade Organization (WTO), 2024)
This paper studies the impact of the process of accession to the WTO on growth rates in a sample of 150 economies. Unlike GATT-era accessions, WTO accessions involve reforms that extend beyond conventional trade liberalization measures. Using information on the pace of negotiations and requests in the working party's meetings, we construct an index that tracks the progress of reforms in the pre-accession period. We estimate that economies that implemented reforms and made deeper commitments during their WTO accession negotiations grew on average 1.5 percentage points faster than they otherwise would have. These results are robust to instrumental variable estimation and falsification tests.
Keywords: F14; F43; F6; 330; WTO accession; structural reforms; trade and growth